Drying and wetting characteristics of a two-layer soil column - Indrawan, I. Gde Budi (2011)
The drying and wetting characteristics of a two-layer soil column consisting of a 50 cm thick soil mixture over a 50 cm thick gravelly sand were investigated in this study. A series of infiltration tests were conducted in the laboratory through an infiltration column apparatus equipped with a tensiometer–transducer system, time-domain reflectometry, and water flow measurement system. Numerical analyses were performed using a finite element model to simulate water infiltration into the laboratory model under steady-state and transient conditions. The experimental data and numerical simulation results showed that static nonequilibrium profiles of pore-water pressure head were developed in the gravelly sand shortly after a drying process was started. The low unsaturated permeability of the gravelly sand resulted in a delay in downward water flow into the lower soil layer during a wetting process portion of the rainfall test.